Decoding a complex record of anthropogenic and natural impacts in the Lake of Cavazzo sediments, NE Italy - Polonia, Alina; Albertazzi, Sonia; Bellucci, Luca Giorgio; Bonetti, Carla; Bonetti, Jarbas; Giorgetti, Giulia; Giuliani, Silvia; Correa, Matthias López; Mayr, Christoph; Peruzza, Laura; Stanghellini, Giuseppe; Gasperini, Luca (Science of the Total Environment, 2021)
The Lake of Cavazzo is a natural, lacustrine basin in the Friuli-Venezia Giulia region (NE Italy), which occupies a fluvio-glacial suspended valley of the Tagliamento river, at the southern front of the Alpine chain. The lake formed after the melting of major glacial tongues at the end of the Last Glacial Maximum, and has been affected in recent years by natural and anthropogenic events, with economic, cultural and environmental consequences. According to local witnesses, the lake environment has changed dramatically after the 1950s, when the basin was connected to a hydroelectric power plant collecting waters from a wider catchment area, as it served as its final discharge basin. In this work, based on a densely-spaced grid of high-resolution seismic reflection profiles complemented by sediment cores, we analysed the uppermost lake stratigraphy, highlighting major changes occurring at a decadal scale. Our main purpose is to verify whether and how the lake sediments record the transition from pristine/natural to artificial conditions, as well as the effects of multiple natural impacts including the 1976–77 Friuli earthquake sequence. The results of our analysis suggest varying environmental conditions of the lake after the 1950s indicated by changing sediment mineralogy, increased deposition of allochthonous clastic sediments, and recurrent episodes of anoxic conditions at the lake's floor, likely triggered by hyperpycnal flows derived from the hydroelectric power plant discharges. We also observe that the effects of the 1976–77 seismic sequence are recorded in the lake as resedimented levels, likely due to shaking, in situ deformation, landslides, and turbidity currents. Our results stress the importance of lacustrine environments as efficient recorders of anthropogenic and natural events.
CRIS-Team Scopus Importer:2021-06-18
Keywords: 1976 Friuli earthquakes; Carnia region; Eastern Alps; Hydroelectric power plant; Lacustrine seismo-turbidite